Identification of natural inhibitors of Entamoeba histolytica cysteine synthase from microbial secondary metabolites - Mori, Mihoko; Jeelani, Ghulam; Masuda, Yui; Sakai, Kazunari; Nakada-Tsukui, Kumiko; Waluyo, Danang; _, Tarwadi; Watanabe, Yoshio; Nonaka, Kenichi; Matsumoto, Atsuko; Ōmura, Satoshi; Nozaki, Tomoyoshi; et al. (Frontiers in Microbiology, 2015)
Amebiasis is a common worldwide diarrheal disease, caused by the protozoan parasite, Entamoeba histolytica. Metronidazole has been a drug of choice against amebiasis for decades despite its known side effects and low efficacy against asymptomatic cyst carriers. E. histolytica is also capable of surviving sub-therapeutic levels of metronidazole in vitro. Novel drugs with different mode of action are therefore urgently needed. The sulfur assimilatory de novo L-cysteine biosynthetic pathway is essential for various cellular activities, including the proliferation and anti-oxidative defense of E. histolytica. Since the pathway, consisting of two reactions catalyzed by serine acetyltransferase (SAT) and cysteine synthase (CS, O-acetylserine sulfhydrylase), does not exist in humans, it is a rational drug target against amebiasis. To discover inhibitors against the CS of E. histolytica (EhCS), the compounds of Kitasato Natural Products Library were screened against two recombinant CS isozymes: EhCS1 and EhCS3. Nine compounds inhibited EhCS1 and EhCS3 with IC50 values of 0.31-490 μM. Of those, seven compounds share a naphthoquinone moiety, indicating the structural importance of the moiety for binding to the active site of EhCS1 and EhCS3. We further screened >9,000 microbial broths for CS inhibition and purified two compounds, xanthofulvin and exophillic acid from fungal broths. Xanthofulvin inhibited EhCS1 and EhCS3. Exophillic acid showed high selectivity against EhCS1, but exhibited no inhibition against EhCS3. In vitro anti-amebic activity of the 11 EhCS inhibitors was also examined. Deacetylkinamycin, deoxyfrenolicin, and nanaomycin A showed more potent amebicidal activity with IC50 values of 0.3-11 μM in the cysteine deprived conditions. The differential sensitivity of trophozoites against deacetylkinamycin in the presence or absence of L-cysteine in the medium and the IC50 values against EhCS suggest the amebicidal effect of deacetylkinamycin is due to CS inhibition